Development and Validation of the Return and Disposal of Unused Medications Questionnaire (ReDiUM) in Malaysia. (November 2018) - Sim, Si Mui; Lai, Pauline Siew Mei; Tan, Kit Mun; Lee, Hong Gee; Sulaiman, Che Zuraini
The aim of our study was to develop and validate the return and disposal of unused medications (ReDiUM), as there are currently no validated tools available (worldwide) to assess this. The ReDiUM was developed by an expert panel. It was then administered to community-dwelling adults, who could understand English, at baseline and 2 weeks later. A total of 338/354 participants agreed to participate (response rate = 95.4%). Flesch reading ease was 60. The overall Cronbach's α was 0.703 (range = 0.609-0.762). At test-retest, κ values ranged from 0.244 to 0.523. Median total knowledge score was 60% (interquartile range = 40% to 70%). The majority of participants (94.4%) knew that improper drug disposal has harmful effects on the environment. However, their knowledge was low (11.2%) regarding the disposal of pressurized metered-dose inhalers in the garbage. The ReDiUM was found to be a valid and reliable instrument to assess the knowledge, attitude, and practice on the ReDiUM in Malaysia.